Investigation of Work-Life Quality and Work-Family Conflict of Nurses Working in Shifts in Terms of Some Variables - Ferhat Daşbilek; Özlem Doğan Yüksekol; İlksen Orhan (Sağlık ve Hemşirelik Yönetimi Dergisi, 2022)
Aim: This research aimed to determine the work-life quality and work-family conflict of nurses working in shifts. Method: This cross-sectional study was conducted with 507 nurses working in a university hospital who volunteered to participate in the study, where 735 nurses were employed. Data were collected via an online questionnaire consisting of three parts. The questionnaire was formed by using the 'Self Description Form, Work-Family Conflict Scale, and Quality of Work Life Scale.' Descriptive statistics, unpaired t-test, one-way analysis of variance (ANOVA), and Tukey test were used in data analysis. Eta squared (η2) and Cohen (d) coefficients were used to calculate the effect size. Results: 74% of the nurses hold a bachelor's degree, 52% are married, and 90,1% work shifts. The study findings specified that the average score of the nurses' Quality of Work Life Scale was 28.578+-5.700. The study findings specified that the average score of the nurses' Work Family Conflict Scale is 20,282+-2,909. It was determined that burnout increased the level of work-family conflict (ß=0,14). The Work-Family Conflict Scale scores of the nurses were related to the clinics where the nurses worked (F=2,807; p<0,05; η2=0,027). Conclusion: It was concluded that as age and working time in nursing ascend, the rate of occupational satisfaction increases. Female nurses' burnout, compassion fatigue, and occupational satisfaction are higher than male nurses. Shift pattern increases work-family conflict and burnout. It is recommended that nurses with high burnout and work-family conflict rates should be provided with psychological support, and working hours should be arranged to increase performance and reduce burnout and work-family conflict.